Identification of gene expression-based prognostic markers in the hematopoietic stem cells of patients with myelodysplastic syndromes - Pellagatti, Andrea; Benner, Axel; Mills, Ken I.; Cazzola, Mario; Giagounidis, Aristoteles; Perry, Janet; Malcovati, Luca; Della Porta, Matteo G.; Jädersten, Martin; Verma, Amit; McDonald, Emma-Jane; Killick, Sally; et al. (Journal of clinical oncology, 2013)
Purpose: The diagnosis of patients with myelodysplastic syndromes (MDS) is largely dependent on morphologic examination of bone marrow aspirates. Several criteria that form the basis of the classifications and scoring systems most commonly used in clinical practice are affected by operator-dependent variation. To identify standardized molecular markers that would allow prediction of prognosis, we have used gene expression profiling (GEP) data on CD34+ cells from patients with MDS to determine the relationship between gene expression levels and prognosis. - Patients and Methods: GEP data on CD34+ cells from 125 patients with MDS with a minimum 12-month follow-up since date of bone marrow sample collection were included in this study. Supervised principal components and lasso penalized Cox proportional hazards regression (Coxnet) were used for the analysis. - Results: We identified several genes, the expression of which was significantly associated with survival of patients with MDS, including LEF1, CDH1, WT1, and MN1. The Coxnet predictor, based on expression data on 20 genes, outperformed other predictors, including one that additionally used clinical information. Our Coxnet gene signature based on CD34+ cells significantly identified a separation of patients with good or bad prognosis in an independent GEP data set based on unsorted bone marrow mononuclear cells, demonstrating that our signature is robust and may be applicable to bone marrow cells without the need to isolate CD34+ cells. - Conclusion: We present a new, valuable GEP-based signature for assessing prognosis in MDS. GEP-based signatures correlating with clinical outcome may significantly contribute to a refined risk classification of MDS.